Sarcopenia Was a Poor Prognostic Predictor for Patients With Advanced Lung Cancer Treated With Immune Checkpoint Inhibitors - Li, Shuluan; Liu, Zhou; Ren, Ya; Liu, Jinying; Lv, Shiqi; He, Pin; Yang, Yajing; Sun, Yanfen; Chang, Jianhua; Luo, Dehong; Cong, Minghua (Frontiers in Nutrition, 2022)
Background : It remains not well known whether skeletal muscle mass (SMM) loss has any impact on the effectiveness of immune checkpoint inhibitors (ICIs) in patients with advanced lung cancer. We aimed to evaluate the association between SMM and clinical outcome of patients with advanced lung cancer receiving ICIs as first line or second line. Methods: From March 1st, 2019 to March 31st, 2021 at our hospital, 34 patients with advanced lung cancer treated with first-line or second-line ICIs were enrolled retrospectively. The estimation of skeletal muscle index (SMI) for sarcopenia was assessed at the level of the third lumbar vertebra (L3) on computed tomography (CT) images obtained within 4 weeks before initiation of ICIs treatment. The impact of sarcopenia (low SMI) on progression free survival (PFS) was analyzed using Kaplan-Meier method and log-rank tests. The effect of various variables on PFS was evaluated using Cox proportional hazards regression model with univariate and multivariate analysis. The impact on treatment response including objective response rate (ORR) and disease control rate (DCR) and immunotherapy-related adverse events (irAEs) between patients with and without sarcopenia was compared by the chi-squared test. The comparison of SMI value between patients with objective response, disease control and those without OR and DC was used student t-test or Mann-Whitney U test. Results: Both in univariate and multivariate analysis, sarcopenia and treatment lines were the predictive factors for PFS (р < 0.05). Patients with sarcopenia had significantly shorter PFS than that of non-sarcopenic ones (6.57months vs. 16.2 months, hazard ratios (HR) = 2.947 and 3.542, and 95% confidence interval (CI): 1.123 - 13.183 and 1.11-11.308, p = 0.022 and 0.033). No significant difference in ORR and irAEs was found. Patients with sarcopenia had lower DCR than those without sarcopenia. The mean SMI value of DCR group and non-DCR group was 32.94 ± 5.49cm2/m2 and 44.77 ± 9.06cm2/m2, respectively (p = 0.008). Conclusions: Sarcopenia before immunotherapy might be a significant predictor for poor prognosis including shorter PFS and lower DCR in patients with advanced lung cancer treated with ICIs as first line or second line.